Efficient Mechanoluminescent Elastomers for Dual‐Responsive Anticounterfeiting Device and Stretching/Strain Sensor with Multimode Sensibility. (25th June 2018) - Wu, Chen; Zeng, Songshan; Wang, Zhaofeng; Wang, Fu; Zhou, Hui; Zhang, Jiachi; Ci, Zhipeng; Sun, Luyi
Abstract: In this work, an environmentally friendly and novel oxide‐based mechanoluminescent material, Sr3 Al2 O6 : Eu 3+, which can serve as the alternative for the widely used but environmentally hazardous transition metal–doped sulfides is reported. This oxide could exhibit highly efficient photoluminescence, but even more efficient mechanoluminescence as embedded into polydimethylsiloxane matrix under mechanical stimulation. The emitting color of the resultant Sr3 Al2 O6 : Eu 3+ /polydimethylsiloxane elastomer composites could be further manipulated by adjusting the synthesis atmosphere of the Sr3 Al2 O6 : Eu 3+ based on its unique self‐reduction characteristic. Moreover, by combining the wavelength selectivity of photoluminescence and dynamic stress response of mechanoluminescence, Sr3 Al2 O6 : Eu 3+ enables the design of two types of intriguing devices. They are a dual‐responsive anticounterfeiting flexible device activated by either photons or mechanics, and a comprehensive stretching/strain sensor capable of sensing both strain level and stretching states. In comparison to the conventional luminescent materials, with a rare combination of efficient photoluminescence, highly sensitive mechanoluminescence, and facile color tunability, Sr3 Al2 O6 : Eu 3+ is much more versatile and ideal for various advanced applications. Abstract : Two types of intriguing flexible devices are developed based on the highly efficient and colorful mechanoluminescence of the oxide‐based materials. They are a dual‐responsive anticounterfeiting flexible device activated by either photons or mechanics, and a comprehensive stretching/strain sensor which is capable of sensing both tensile strain level and stretching states.